Respon pertumbuhan tanaman ubi jalar (Ipomea batatas L.) pada sistem pola tanam monokultur dan tumpangsari dengan tanaman jagung (Zea mays L.) di lahan PT. Koperasi Eiber Shuth Coklat Ransiki Kabupaten Manokwari Selatan - Muyan, Yaved; Asjerem, Fenny S. J.; Makhroji, Lanang Ari (Fakultas Pertanian Universitas Papua, 2023)
This research aimed to determine how sweet potato growth responds to a monoculture cropping system and intercropping with corn. This research was carried out for 4 months December 2021 to April 2022 on the land of PT. Eiber Shuth Coklat Ransiki (Cokran) Cooperative in South Manokwari Regency. This research conducted in Randomized Group Design consisting of two treatments of cropping patterns, namely monoculture and intercropping patterns. The variables observed were length of tendrils, number of leaves, number of branches, fresh weight and dry weight of sweet potato grown in two different cropping patterns. The results of the tabulated analysis showed that the number of leaves, number of branches, length of tendrils and dry weight of sweet potato plants cultivated in monoculture was better than in an intercropping pattern with corn. However, the fresh weight of sweet potato in the intercropping pattern with corn is higher compared to those from the monoculture.